Association between comorbid mental illness and preceding emergency department visits in unplanned admissions - Ayako Okuma; Mikio Nakajima; Tomohiro Sonoo; Kensuke Nakamura; Tadahiro Goto (Acute Medicine & Surgery, 2023)
Abstract Aim To investigate the association between comorbid mental illness and preceding emergency department (ED) visits in patients with unplanned admission. Methods This is a retrospective observational study using data from the EDs of three large tertiary medical facilities in Japan. We included adult patients who were admitted to these hospitals via the ED from 2017 to 2020. To investigate whether patients with mental illness were more likely to have preceding ED visits within 30 days prior to unplanned admissions compared with those without, we used univariate and multivariable logistic regression models. In the multivariable model, we adjusted for age category, gender, facility, year, and ambulance use. Results Out of 15,429 total admissions, 766 (5.0%) cases had documented comorbid mental illness and 14,663 (95.0%) did not. The prevalence of preceding ED visits among patients with mental illness was significantly higher than in those without (17.1% vs 8.8%; unadjusted odds ratio 2.15, 95% confidence interval [CI] 1.76–2.61; P < 0.001). This association was more prominent in the multivariable regression model (adjusted odds ratio 2.40, 95% CI 1.97–2.94; P < 0.001). Conclusions The presence of mental illness was significantly associated with a higher prevalence of preceding ED visits within 30 days prior to the unplanned admission. The result suggests that physicians should be more cautious in discharging patients with mental illness from the EDs and in providing care after ED discharge.